THE REALIZATION OF REQUESTING SPEECH ACTS IN DEMANDING FULFILLMENT OF PROMISES IN INDONESIAN: A Case Study at a State University in Bandung - Heri Ismanto, - (2011)
This paper investigates the realization of requesting speech act in demanding fulfillment of promises in Indonesian. The study employed qualitative research design characterizing principles of case study and uses Blum-Kulka (1989) and Searle (1969) frameworks to analyze the data. Combining the Blum-Kulka's suggestion on CCRSAP with strategies of request in Indonesian suggested by Aziz (2005) help the writer to find out patterns/strategies used. The respondents of this study are the students of Indonesia University of Education and all of them are native of Indonesian. The study reveals that the most common request strategy used by Indonesian to demand fulfillment of promises is strong hint. It means that indirect strategy frequently used by Indonesian. The common patterns revealed by this study prove that speaker's educational background does not influence someone in realizing request strategy.